Accelerated biodegradation of selected nematicides in tropical crop soils from Costa Rica - Chin Pampillo, Juan Salvador (2014)
Degradation and mineralization behavior of select ed nematicides was studied in soil samples from fields culti vated with banana, potato, and coffee. Degradation assays in most of the studied soils revealed shorter half-lives for carbofuran (CBF) and ethoprophos (ETP) in samples with a history of treatment with these compounds, which may have been caused by enhanced biodegradation. A short half-life value for CBF degradation was also observed in a banana field with no previous exposure to this pesticide, but with a recent application of the carbamate insecticide oxamyl, which supports the hypothesis that preexposure to oxamyl may cause microbial adaptation towards degradation of CBF, an obser vation of a phenomenon not yet tested according to the liter ature reviewed. Mineralization assays for CBF and terbufos (TBF) revealed that history of treatment with these nemati cides did not cause higher mineralization rates in preexposed soils when compared to unexposed ones, except in the case of soils from coffee fields. Mineralization half-lives for soils unexposed to these pesticides were significantly shorter than most reports in the literature in the same conditions. Mineralization rates for soils with a previous exposure to these pesticides were also obtained, adding to the very few reports found. This paper contributes valuable data to the low number of reports dealing with pesticide fate in soils from tropical origin.